Logic Interrelation of Embedding the Word "Kyai" in the Gamelan Ensamble (A Cultural Deconstruction Process) - Suhendi Afryanto; Pepep Didin Wahyudin (Pascasarjana ISBI Bandung Conference Series, 2025)
Some Heirloom Gamelan which are considered sacred by some cultural areas, have a place of honor with the title "Kyai". This phenomenon must be able to be read in the context of local culture which is currently still being used by the supporting communities. For example, in the palace areas which are quite large and still exist today, namely the Yogyakarta Palace and the Surakarta Palace. Outside the palace area, a similar designation occurs in wider society with the term "Ki". The reading in question can be approached as a theoretical proposition through Derrida's theory of Deconstruction with its binary option which allows for two-way conclusions, namely factual justification or rejection of those deemed too far-fetched. To reveal all the premises that might occur in people's lives, finally a research was carried out using qualitative methods with an emic approach which took data sources through literature studies and Personal Narratives. Keywords: Gamelan art; cultural wisdom